2020
DOI: 10.1111/njb.02761
|View full text |Cite
|
Sign up to set email alerts
|

Impatiens bomiensis (Balsaminaceae), a new species from Xizang, China

Abstract: Impatiens bomiensis, a new species of Balsaminaceae from Bomi County, Xizang, China, is described and illustrated. This new species is similar to Impatiens fragicolor based on morphological characters and molecular data, but differs in the shape of the lower sepal, the dorsal petal and the number of globose glands at petiole base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Specimens were collected, preserved, and deposited in the Herbarium of Wuhan Botanical Garden, Chinese Academy of Sciences (HIB) for further identification. We then dissected the flower and carefully reviewed related literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]36,37] and herbaria specimens in a bid to ascertain the identity of the collected species. However, we were unable to match the new plants with any described species based on morphology.…”
Section: Identification and Description Of New Taxonmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens were collected, preserved, and deposited in the Herbarium of Wuhan Botanical Garden, Chinese Academy of Sciences (HIB) for further identification. We then dissected the flower and carefully reviewed related literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]36,37] and herbaria specimens in a bid to ascertain the identity of the collected species. However, we were unable to match the new plants with any described species based on morphology.…”
Section: Identification and Description Of New Taxonmentioning
confidence: 99%
“…The Flora of China lists 227 species, of which 187 are endemic [14]. According to Du et al [15], a total of 69 new taxa of Impatiens have been described in China between 2000 and 2019, and 13 new taxa [16][17][18][19][20][21][22][23][24][25][26][27][28] and three new records [28][29][30] have been published in the last two years, bringing the total species reported for China to nearly 290.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its unique landform and variable climate, southwestern China (covering the provinces of Sichuan, Yunnan, Guizhou, Tibet and Chongqing) is home to a variety of Impatiens species. In recent years, numerous new species have successively been discovered in this area (Cai et al 2015, Luo et al 2015a, b, Tan et al 2015, Ding et al 2016, Guo et al 2016, Xia et al 2019, Peng et al 2020, 2021a, b, Xue et al 2020, Zhang et al 2020, Gu et al 2021, Liao et al 2021, Song et al 2021a, b, Ren et al 2022, Wang et al 2022, Yuan et al 2022a), increasing China's Impatiens species to 352 (Yuan et al 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Chen Yilin (Chen et al 2008) reported 228 known species of Impatiens in China, of which 187 are endemic, while Yu Shengxiang (Yu 2012) reported the discovery of approximately 270 species in China. With the expansion of our research, in recent years numerous new species have been successively found and documented (Peng et al 2019, Zhang et al 2020a, b), with over 20 new species discovered between 2019 and 2021 (Xia et al 2019a, b, Gan and Li 2020a, b, Gan et al 2020, Lu et al 2020, Peng et al 2020, 2021a, b, Qin et al 2020, Wang et al 2020a, Xue et al 2020, Zhang et al 2020a, Zou et al 2020, Liao et al 2021, Song et al 2021a, b, c). At present, approximately 290 species of Impatiens are documented from China.…”
Section: Introductionmentioning
confidence: 99%